Evaluation and projection of mean surface temperature using CMIP6 models over East Africa. (September 2021) - Ayugi, Brian; Ngoma, Hamida; Babaousmail, Hassen; Karim, Rizwan; Iyakaremye, Vedaste; Lim Kam Sian, Kenny T.C.; Ongoma, Victor
Abstract: This study evaluates the historical mean surface temperature (hereafter T2m) and examines how T2m changes over East Africa (EA) in the 21st century using CMIP6 models. An evaluation was conducted based on mean state, trends, and statistical metrics (Bias, Correlation Coefficient, Root Mean Square Difference, and Taylor skill score). For projections over EA, five best performing CMIP6 models (based on their performance ranking in historical mean temperature simulations) under the shared socioeconomic pathways SSP2-4.5 and SSP5-8.5 scenarios were employed. The historical simulations reveal an overestimation of the mean annual T2m cycle over the study region with fewer models depicting underestimations. Further, CMIP6 models reproduce the spatial and temporal trends within the observed range proximity. Overall, the best performing models are as follows: FGOALS-g3, HadGEM-GC31-LL, MPI-ESM2-LR, CNRM-CM6-1, andIPSL-CM6A-LR. During the three-time slices under consideration, the Multi Model Ensemble (MME) project many changes during the late period (2080–2100) with expected mean changes at 2.4 °C for SSP2-4.5 and 4.4 °C for the SSP5-8.5 scenario. The magnitude of change based on Sen's slope estimator and Mann-Kendall test reveal significant increasing tendencies with projections of 0.24 °C decade-1 (0.65 °C decade-1) under SSP2-4.5(SSP5-8.5) scenarios. The findings from this study illustrate higher warming in the latest model outputs of CMIP6 relative to its predecessor, despite identical instantaneous radiative forcing. Highlights: Historical and future changes in mean surface temperature is examined using CMIP6 models in EA region. Best models include FGOALS-g3, HadGEM-GC31-LL, MPI-ESM2-LR, CNRM-CM6-1, and IPSL-CM6A-LR. Projection shows mean changes at 2.4 °C (4.4 °C) for SSP2-4.5 (SSP5-8.5) scenarios during 2080–2100. Significant increasing trends at 0.24 °C (0.65 °C decade-1) under SSP2-4.5 (SSP5-8.5) scenarios. The study shows higher warming in CMIP6 over the study region.